Play frames and social identities : contact encounters in a Greek primary school - Lytra, Vally (Pragmatics & beyond., 2007)
This book is a sociolinguistic study of children's talk and how they interact with one another and their teachers in multilingual, multicultural and multiethnic schools. It is based on tape recordings and ethnographic observations of majority Greek and minority Turkish-speaking children at an Athens primary school. It offers the reader a unique look into the ways in which children draw upon their rich interactional histories and share, transform and recontextualize linguistic and other semiotic resources in circulation to construct play frames and explore, adopt, resist available as well as no.